2018
DOI: 10.20411/pai.v3i1.228
|View full text |Cite
|
Sign up to set email alerts
|

ADCC-Mediated CD56dim NK Cell Responses Are Associated with Early HBsAg Clearance in Acute HBV Infection

Abstract: BackgroundHepatitis B virus (HBV) affects up to 400 million people worldwide and accounts for approximately one million deaths per year from liver pathologies. Current treatment regimens are effective in suppressing viremia but usually have to be taken indefinitely, warranting research into new therapeutic approaches. Acute HBV infection in adults almost universally results in resolution of viremia, with the exception of immunocompromised persons, suggesting that the immune response can functionally cure or ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Interestingly, the cytolytic CD56dim NK-cell subset in the peripheral blood is selectively activated and expands in acute HBV infection, displaying distinct phenotypic and functional profiles associated with efficient and early control of HBV. This implicates NK cell cytolytic responses in the early containment and resolution of HBV infection [ 60 , 96 ]. Furthermore, early clearance of hepatitis B surface antigen (HBsAg) can be predicted by a distinct CD56dim NK cells phenotypic profile [ 60 , 96 ].…”
Section: Hbv Increases the Number Of Cd56dim Nk Cells In Acute Infectmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the cytolytic CD56dim NK-cell subset in the peripheral blood is selectively activated and expands in acute HBV infection, displaying distinct phenotypic and functional profiles associated with efficient and early control of HBV. This implicates NK cell cytolytic responses in the early containment and resolution of HBV infection [ 60 , 96 ]. Furthermore, early clearance of hepatitis B surface antigen (HBsAg) can be predicted by a distinct CD56dim NK cells phenotypic profile [ 60 , 96 ].…”
Section: Hbv Increases the Number Of Cd56dim Nk Cells In Acute Infectmentioning
confidence: 99%
“…This implicates NK cell cytolytic responses in the early containment and resolution of HBV infection [ 60 , 96 ]. Furthermore, early clearance of hepatitis B surface antigen (HBsAg) can be predicted by a distinct CD56dim NK cells phenotypic profile [ 60 , 96 ]. In HBV-infected patients, memory-like FcεRIγ-/CD56dim NK cells with higher NKG2C and lower NKG2A expression undergo increased cytokine responses and CD16-mediated ADCC compared to conventional CD56dim NK cells following exposure to HCMV [ 97 ].…”
Section: Hbv Increases the Number Of Cd56dim Nk Cells In Acute Infectmentioning
confidence: 99%
“…Functional analysis revealed that elevated antibody-mediated cytotoxicity degranulation can represent a key mechanism in early clearance. On the other hand, higher cytokine production was detected in the case of later clearance, which suggests that ADCC-mediated NK cell killing is more effective than non-cytopathic mechanisms in the early control of acute HBV infection [46].…”
Section: Nk Cells In Hbv Infectionmentioning
confidence: 99%
“…Natural killer (NK) cells are endowed with antiviral properties such as IFN-γ and TNF-α secretion as well as cytotoxicity that could contribute to HBV clearance ( Fisicaro et al, 2019 ). In patients, NK cells are activated during acute HBV infection before the onset of adaptive immunity ( Dunn et al, 2009 ; Fisicaro et al, 2009 ; Zhao et al, 2012 ; Lunemann et al, 2014 ; Yu et al, 2018 ). However, in the chronic phase of the disease, NK cells present impaired functions, which could contribute to viral persistence.…”
Section: Introductionmentioning
confidence: 99%